Diagnosis of Disseminated Toxoplasmosis by Polymerase Chain Reaction in Bronchoalveolar Lavage Fluid of a Patient with AIDS - Dora, Jose Miguel; Geib, Guilherme; de-Paris, Fernanda; Machado, Alice Beatriz; Furlanetto, Tania Weber; de Souza, Carolina Fischinger Moura; dos Santos, Rodrigo Pires (Clinical and Biomedical Research, 2009)
Pulmonary toxoplasmosis is a challenging diagnosis in immunosuppressed patients with nonspecific clinical picture and radiologic findings. We present a case of pneumonia due to Toxoplasma gondii diagnosed by polymerase chain reaction (PCR) in the bronchoalveolar lavage (BAL) fluid of a patient with acquired immunodeficiency syndrome (AIDS). Coinfection with Pneumocystis jirovecii was found in the same specimen. Direct examination and culture for bacteria, mycobacteria and other fungus were negative. Despite the intensive management, respiratory compromise evolved rapidly, with the need for ventilatory support. Acute respiratory distress syndrome developed, and the patient died of multiple organ failure. This case illustrates that a high index of suspicion is necessary for diagnosis of pulmonary toxoplasmosis, a potentially fatal condition. Due to high diagnostic performance, PCR in BAL fluid should be included in the evaluation of immunosuppressed patients with nonspecific pulmonary diseases.